An electrochemical investigation of rutile TiO2 microspheres anchored by nanoneedle clusters for sodium storage. Issue 24 (28th June 2015) - Zhang, Yan; Pu, Xuli; Yang, Yingchang; Zhu, Yirong; Hou, Hongshuai; Jing, Mingjun; Yang, Xuming; Chen, Jun; Ji, Xiaobo
<x xml:space="preserve">Abstract</x> Rutile TiO2 microspheres anchored by nanoneedle clusters are successfully employed as anodes for sodium-ion batteries for the first time, and manifested excellent sodium storage properties.